Credit migration and covered interest rate parity - Liao, Gordon Y. (Journal of Financial Economics, 2020)
This paper examines the joint determination of deviations in long-term covered interest rate parity and differences in the credit spread of bonds of similar risk but different currency denomination. These two pricing anomalies are highly aligned in both the time series and the cross-section of currencies. The sum of these two pricing deviations—the corporate basis—represents the currency-hedged borrowing cost difference between currency regions and explains up to a third of the variation in the aggregate corporate debt issuance flow. I show that arbitrage aimed at exploiting one type of security anomaly can give rise to the other.